Standardization of Enzymatic Diagnostic Kit based method for cholesterol estimation in Butter, Kalakand, Khoa and Paneer - Parmar, Yogesh; Sharma, Vivek (Indian Journal of Dairy Science, 2016)
The objective of this study were to standardize the protocol for cholesterol quantification in dairy based products (butter, kalakand, khoa and paneer) using enzymatic diagnostic kit (EDK) assay. Practically about 0.15-0.2 g product was saponified using different methanolic KOH (2.5%, 5% and 7.5%) as well as at different saponification temperature (800C, 850C and 900C) for 20 min. followed by extraction of unsaponifiable in hexane. An aliquot of unsaponifiable fraction was evaporated at 500-650C and cholesterol estimation was done using EDK. For standardization of protocol recovery trials also conducted in dairy based products at different methanolic KOH as well as at different saponification temperature. The optimized conditions for rapid saponification of Dairy products were found to be the use of 5% methanolic KOH and heating to 900C for 20 min., wherein the per cent recovery in case of butter, kalakand, khoa and paneer were to the tune of 100.13±0.70; 100.25±0.58; 100.54±0.51; 97.99±0.28, respectively. Recovery studies clearly indicated that developed EDK based method is a choice for the rapid determination of cholesterol content in selected indigenous dairy products. On using the above said optimized saponification conditions the average cholesterol content estimated using EDK method in butter, kalakand, khoa and paneer was 277.72, 76.34, 95.22 and 79.57 mg/100 g product, respectively. Developed EDK method can be used as a routine method to test the cholesterol content in indigenous dairy products to measure the batch to batch variation.